Kindlin-2 modulates MafA and β-catenin expression to regulate β-cell function and mass in mice - Ke Zhu (Nature Portfolio, 2020)
Beta cell dysfunction and reduction in beta cell mass are hallmark events in the pathogenesis of diabetes mellitus. We identify focal adhesion protein Kindlin-2 as a key factor that controls insulin synthesis and secretion and beta cell mass by modulating MafA and beta-catenin proteins in pancreatic beta cells.